Development of QR code based library management system for managing building plan from HR department at Ranhill Holdings Berhad / Nur Husnina Saharuddin - Saharuddin, Nur Husnina (2017)
This chapter provides the background and rationale for the study. It includes background of study, highlight the problem faced in managing building plans, research objectives, and aim of the project, research scope, significance of the project as well as research expected outcomes.